A study on the factors influencing green cosmetics purchasing behaviour among the residents of Apartment Sri Indah, Selangor / Nurul Amirah Awang Suhaimi and Nur Alis Nabila Md Yusri - Awang Suhaimi, Nurul Amirah; Md Yusri, Nur Alis Nabila (2022)
The study's aim was to investigate the influence of brand awareness, brand loyalty, and perceived quality in affecting green cosmetics purchasing behaviour among residents of Apartment Sri Indah in Selangor. The research was carried out from March 2021 to February 2022.This study used a convenience sampling technique in collecting the survey data. The result of the study revealed three important findings. First, most of the respondents were concerned and want to engage in purchasing green cosmetics and there is a significant and strong relationship with the green cosmetics purchasing behavior. Second, there is a relationship between brand awareness, brand loyalty and perceived quality on green cosmetics purchasing behavior among the residents of Apartment Sri Indah, Selangor because most of the people are concerned about all of these factors before making a purchase on green cosmetics. Third, most of the people are influence in purchasing green cosmetics based on their brand loyalty and there is a strong relationship on brand loyalty factor compared to other factors in influencing green cosmetics purchasing behavior. As a result, this research demonstrates and gives some insights, as well as building on the literature in the areas of industrial management, environmental management, and any respective interested parties.